Effect of an Appearance-Based vs. a Health-Based Sun-Protective Intervention on French Summer Tourists' Behaviors in a Cluster Randomized Crossover Trial: The PRISME Protocol - Durand, Cécile; Catelinois, Olivier; Bord, Apolline; Richard, Jean-Baptiste; Bidondo, Marie-Laure; Ménard, Colette; Cousson-Gélie, Florence; Mahé, Emmanuel; Mouly, Damien; Delpierre, Cyrille (Frontiers in Public Health, 2020)
Background Sun exposure has short-and long-term adverse effects on eyes, skin and the immune system. The most serious effect, melanoma, is largely attributable to natural ultraviolet radiation. Its prevalence is steadily increasing in fair-skinned populations in most European countries. Despite annual prevention campaigns, the French population continues to be overexposed to the sun and under-protected. Social and psychosocial characteristics may play an important role in sun protection determinants. Overexposure is partially motivated by a desire to tan oneself for aesthetic reasons. During summer, intense exposure constitutes a major risk factor for melanoma, making tourists a particularly high-risk population. Literature reviews concluded that appearance-based interventions highlighting the aesthetic effects of sun exposure on skin photoaging showed promise in terms of improving sun-exposure and sun-protection behaviors, especially among younger people, but that more rigorous studies were needed. In this context, we implemented the PRISME study to: -identify the determinants, in particular social and psychosocial, of sun-protection of French summer tourists visiting the Mediterranean coastline; -design two prevention interventions grounded in psychosocial theories; -compare the impact of both interventions on tourists' sun-protection behaviors, and identify the determinants influencing this impact. This paper present the methodology of the PRISME study.During summer 2019, we conducted a cluster randomized crossover trial to compare two prevention interventions, one based on health-related messages (health effects information, phototype calculation), the other on appearance-related messages (photoaging information, ultraviolet photography), among French tourists aged 12 to 55 years old in coastline campsites in the French region of Occitanie. Both interventions were anchored in the theory of planned behavior and in the transtheoretical model. The interventions' impact was measured using face-to-face questionnaires and skin color measurements both immediately before and 4 days after the interventions. A second follow-up, using an online questionnaire, will be conducted in September 2020 to measure the longer-term effects of both interventions.Despite certain study limitations, PRISME take into consideration several known methodological gaps. The study's results will enable to evaluate the efficacy of the promising appearance-based approach in France, and to identify vulnerable sub-populations and mechanisms to improve sun-protection behaviors of French tourists.